Strategi Guru dalam Meningkatkan Hasil Belajar Peserta Didik - Anggi Afrina Rambe; Wirdati Wirdati (An-Nuha, 2022)
This study aims to analyze teacher strategies in improving student learning outcomes in Islamic religious education subjects. This research uses a qualitative method with a case study approach, research data is taken through direct interviews with five informants (school principals, curriculum representatives, three Islamic religious education teachers) who were selected using a purposive sampling technique. To strengthen the interview data, the writer made observations by being directly involved in the learning process in the classroom. All interview and observation data were then analyzed thematically using the Miles and Huberman method. Overall, the research findings found three teacher strategies in improving student learning outcomes in Islamic religious education subjects. The three strategies are: i) providing material according to the ability of students, ii) providing additional learning time, iii) cooperating with homeroom teachers and parents. The three strategies in this study can be used as reference material for other teachers in improving student learning outcomes in Islamic religious education subjects.